Global Liquidity Transmission to Emerging Market Economies, and Their Policy Responses - Choi, Woon (IMF Working Papers; Working Paper ;, 2017)
This paper distills and identifies global liquidity (GL) momenta from the macro-financial data of advanced economies through a factor model with sign restrictions as policy-driven, market-driven, and risk averseness factors. Using a panel factor-augmented VAR, we investigate responses of emerging market economies (EMEs) to GL shocks. A policy-driven liquidity increase boosts growth in EMEs, elevating stock prices and currency values, while a risk averseness rise has an opposite effect. A market-driven GL expansion boosts stock markets and lowers funding costs, promoting competitiveness and current account. Inflation targeting EMEs fare better than EMEs under alternative regimes with respect to macrofinancial volatility.